An Increased Abundance of Clostridiaceae Characterizes Arthritis in Inflammatory Bowel Disease and Rheumatoid Arthritis: A Cross-sectional Study. Issue 5 (12th October 2018) - Muñiz Pedrogo, David A; Chen, Jun; Hillmann, Benjamin; Jeraldo, Patricio; Al-Ghalith, Gabriel; Taneja, Veena; Davis, John M; Knights, Dan; Nelson, Heidi; Faubion, William A; Raffals, Laura; Kashyap, Purna C
Abstract: Background: Inflammatory bowel diseases (IBDs) are a group of heterogeneous inflammatory conditions affecting the gastrointestinal tract. Although there is considerable evidence linking the gut microbiota to intestinal inflammation, there is limited knowledge on its potential role in the development of extraintestinal manifestations of IBD. Methods: Four groups of patients were included: IBD-associated arthropathy (IBD-A); IBD without arthropathy (IBD-N); rheumatoid arthritis (RA); and non-IBD, nonarthritis controls. DNA from stool samples was isolated and sequenced using the Illumina platform. Paired-end reads were quality-controlled using SHI7 and processed with SHOGUN. Abundance and diversity analyses were performed using QIIME, and compositional biomarker identification was performed using LEfSe. Results: One hundred eighty patients were included in the analysis. IBD-A was associated with an increased abundance of microbial tyrosine degradation pathways when compared with IBD-N ( P = 0.02), whereas IBD-A and RA patients both shared an increased abundance of Clostridiaceae when compared with controls ( P = 0.045). We found that history of bowel surgery was a significant source of variability ( P = 0.001) among all IBD patients and was associated with decreased alpha diversity and increased abundance of Enterobacteriaceae ( P = 0.004). Conclusions: An increased abundance of gut microbial tyrosine degradation pathways was associated with IBD-A. An increased abundance of Clostridiaceae was shared by both IBD-A and RA patients and suggests a potentially common microbial link for inflammatory arthritis. The increased abundance of Enterobacteriaceae, previously reported in IBD, may be due to the effects of previous bowel surgery and highlights the importance of controlling for this variable in future studies.